Responsibilities of public authorities in the field of recycling of end-of-life - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2012)
Public administration bodies have within their jurisdiction the authority to administratively regulate the recycling of end-of-life vehicles. The granting of such powers is the result of the effects of regulation of the progress of civilization in the production, use, and ending of the life of a vehicle. Therefore, to ensure against a withdrawal of vehicles from the market that was inconsistent with environmental standards, the legislature standardized the process, leaving it in the hands of public authorities.